Water Annealing of TiO2 Nanotubes for Photocatalysis Revisited - Fu, Fan; Cha, Gi; Denisov, Nikita; Chen, Yuyue; Zhang, Yan; Schmuki, Patrik (ChemElectroChem, 2020)
Over the past years, so-called water annealing of TiO2 nanotube (NT) arrays has attracted considerable attention as a tool to enhance the nanotubes’ photocatalytic properties. The present work investigates the effect of different water-annealing treatments on TiO2 nanotubes and compares it to thermally annealed tubes. We find that the most effective water annealing is water immersion of TiO2 NT arrays at 70 °C for several days. The two main effects are i) a partial crystallization of the tubes to anatase, and ii) an etching of the tube walls that leads to a roughening of the walls and, thus, to a higher surface area. Under the best conditions, water annealing is almost as effective in providing enhanced photocatalytic AO7 degradation as a classic thermal annealing of the tubes. We, however, find that water annealed tubes – due to their only partial crystallization – do not perform well when used as photoelectrodes. For photocatalysis, most efficient is a combination of water annealing, followed by thermal annealing, which provides both a larger surface area and a high crystallinity.
CRIS-Team Scopus Importer:2020-07-24
Keywords: anodization; crystallinity; photocatalytic reaction; TiO; water annealing